Muslim Students’ Verbal Creativity and Learning Skills for Counseling Program Planning - Hartini Hartini; Hasta Purnaputra; Edi Wahyudi; Wael Algommaly (State Islamic University (UIN) Salatiga, 2026)
This study examined Muslim postgraduate students’ verbal creativity and learning skills as an empirical basis for designing data-based guidance and counseling programs in Islamic higher education. A quantitative descriptive design was employed, involving 18 postgraduate students selected through saturated sampling. Data were collected using the Verbal Creativity Test and a 63-item Learning Skills Questionnaire in Higher Education, which demonstrated excellent reliability (Cronbach’s alpha = .951). The verbal creativity test showed that 66.7% of students were classified in the average category, 27.8% were below average, and 5.5% were borderline. These findings indicate that most students had adequate verbal creativity, although some still showed limitations in fluency, flexibility, originality, and elaboration. The learning skills profile showed varied achievement across six dimensions: selecting and completing study loads, participating effectively in lectures, memory and concentration, completing assignments and written work, test-taking skills, and learning from and with others. The lowest areas of concern were assignment completion, academic writing, learning resilience, reference use, and collaborative learning. These results suggest that students require structured support in academic writing, learning regulation, reference searching, test preparation, self-concept development, and collaborative learning. The findings provide a basis for designing guidance and counseling services through information services, content mastery, individual counseling, group guidance, and group counseling. The proposed program integrates psychological support with relevant Qur’anic and hadith-based values to strengthen students’ self-regulation, academic responsibility, and verbal creativity. This study contributes to the development of data-based counseling services for Muslim students in higher education.